Quantum leap. Season 2 [videorecording (DVD)] - Bellisario, Donald P.; Whitmore, James, 1948-; Bakula, Scott; Stockwell, Dean, 1936-2021 (Mill Creek Entertainment, 2016)
Reunite with Dr. Sam Beckett, a scientist who never knows whose body he is going to "leap" into next or when, where and at what moment in time he may find himself. Who will he be next? An undercover cop. A blind pianist. A harassed secretary. It's up to Sam to change the history of each person for the better, and hopefully complete the mission that will someday take him home.